Ventricular B1+ perturbation at 7 T – real effect or measurement artifact?. (14th April 2014) - Brink, Wyger M.; Börnert, Peter; Nehrke, Kay; Webb, Andrew G.
<x xml:space="preserve">Abstract</x> The objective of this work was to explore the origin of local B1+ perturbations in the ventricles measured at 7 T. The B1+ field in the human brain was mapped using four different MRI techniques: dual refocusing echo acquisition mode (DREAM), actual flip‐angle imaging (AFI), saturated double‐angle method (SDAM) and Bloch–Siegert shift (BSS). Electromagnetic field simulations of B1+ were performed in male and female subject models to assess the dependence of the B1+ distribution on the dielectric properties of cerebrospinal fluid and subject anatomy. All four B1+ mapping techniques, based on different B1+ encoding mechanisms, show 'residual' structure of the ventricles, with a slightly enhanced B1+ field in the ventricles. Electromagnetic field simulations indicate that this effect is real and arises from the strong contrast in electrical conductivity between cerebrospinal fluid and brain tissue. The simulated results were in good agreement with those obtained in three volunteers. Measured local B1+ perturbations in the ventricles at 7 T can be partially explained by the high contrast in electrical conductivity between cerebrospinal fluid and white matter, in addition to effects related to the particular B1+ measurement technique used. Copyright © 2014 John Wiley & Sons, Ltd.